Preparation and characterization of self-assembled nanoparticles based on glycol chitosan bearing adriamycin - Park, Jae Hyung; Cho, Yong Woo; Son, Yoen Ju; Kim, Kwangmeyung; Chung, Hesson; Jeong, Seo Young; Choi, Kuiwon; Park, Chong Rae; Park, Rang-Woon; Kim, In-San; Kwon, Ick Chan (SPRINGER, 2006)
An anthracycline drug, adriamycin, was chemically conjugated onto the backbone of glycol chitosan via an acid-labile cis-aconityl linkage. The physicochemical characteristics of the glycol chitosan-adriamycin (GC-ADR) conjugates were investigated by dynamic light scattering, atomic force microscopy, and fluorescence spectroscopy. The GC-ADR conjugates were capable of fort-ning nano-sized self-aggregates in an aqueous medium, when the adriamycin content in the conjugate was in the range of 2.0-5.0 wt.%. The self-aggregates were spherical in shape, and had mean diameters of 238-304 nm, depending on the adriamycin content. The critical aggregation concentrations of the conjugates, estimated by the fluorescence quenching method, were as low as 1.0-2.5 x 10(-2) mg/ml. The size of self-aggregates was not affected by the polymer concentration m the range from 50 to 2,000 mu g/ml, and was maintained up to 8 days in phosphate-buffered saline (pH 7.4), indicating high colloidal stability. The release of adriamycin from self-aggregates was significantly dependent on the pH of the medium due to the cis-aconityl linkage; e.g., the amount of adriamycin released for 4 days was 7.3 +/- 0.3% at pH 7, whereas it was 29.3 +/- 1.9% at pH 4. The cell viability results demonstrated that free adriamycin shows more potent cytotoxicity than the conjugates, primarily attributed to the sustained release of adriamycin from self-aggregates. In conclusion, the self-aggregates, formed by GC-ADR conjugates, might be useful for the site-specific delivery of adriamycin in a sustained manner.
Keywords: POLYION COMPLEX MICELLES; PH-SENSITIVE LINKAGE; POLYMERIC MICELLES; IN-VITRO; PHYSICOCHEMICAL CHARACTERISTICS; MACROMOLECULAR THERAPEUTICS; HYDROGEL NANOPARTICLES; ANTITUMOR EFFICACY; BLOCK-COPOLYMERS; DOXORUBICIN